Астрономия - Аткинсон Стюарт (Серия "Энциклопедия окружающего мира", 2001)
На обл. автор не указан Экземпляры: ф.8 (26.02.2003) / Инвентарный номер: 34583 / Цена: 86.25 / Авт.знак: А 92 / ГРНТИ: 41 / ББК: 22.6